Vitamin C retention in bottled tomato jam - Dia, Beatrice E.; Rumbaoa, Rowena Grace O. (2002., 2002)
ABSTRACT At present there is no tomato jam on the Filipino table. Yet, tomato has all the qualities that make a good jam. It is rich in taste and nutrients, has the required pectin content for jam making, and the fruit itself is widely available in the country. This study seeks to demonstrate that a tomato jam is indeed feasible and attractive, with its taste and nutritious properties, especially vitamin C, harnessed to the fullest. A tomato jam was developed in this study using two established standardized jam formulations as bases. Using structured sensory analyses, the better of the two was chosen and its desirable characteristics optimized further. Three samples of this optimized formulation was reproduced and tested for microbiological, physico-chemical and sensory properties, and each sample was compared to each other. As there were no significant deviations in these established properties and parameters among the three samples, the formulation was taken to be standard. It was found out that tomato is a feasible raw material for making jams and it is deemed acceptable based on the sensory analyses. Moreover, physico-chemical and microbiological analyses reveal that it is a high acid product with an average pH of 3.8, % titrable acidity of 0.67 expressed as citric acid, soluble solids of 72-73° brix and with extremely low counts of yeast and molds. Further, another production run was made on this standardized formula and tested for vitamin C retention. The results reveal that the product contains all the needed qualities for a good and tasty jam but there were significant losses, an average of 34% on its vitamin C content during processing.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Jam; Tomatoes